2008
DOI: 10.1161/strokeaha.107.497271
|View full text |Cite|
|
Sign up to set email alerts
|

Antiplatelet Therapy for Secondary Prevention of Noncardioembolic Ischemic Stroke

Abstract: Abstract-For

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 59 publications
0
25
0
2
Order By: Relevance
“…Actually, the benefits of aspirin in reducing recurrent stroke (–7/1,000) or death/dependency (–13/1,000) were negated by the increased intracranial (+2/1,000) or extracranial hemorrhages (+4/1,000) [3]. Characteristically, cilostazol does not prolong the bleeding time compared with aspirin or clopidogrel [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, the benefits of aspirin in reducing recurrent stroke (–7/1,000) or death/dependency (–13/1,000) were negated by the increased intracranial (+2/1,000) or extracranial hemorrhages (+4/1,000) [3]. Characteristically, cilostazol does not prolong the bleeding time compared with aspirin or clopidogrel [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, antiplatelet trials in acute stroke are rare, and the efficacy and safety have only been proven for aspirin. Aspirin reduced recurrent stroke or death; however, the net benefit was small because of symptomatic hemorrhages [1,2,3]. In addition, about 8–18% of patients suffer from recurrent vascular events including stroke while taking aspirin [4], and some patients are intolerant to or have contraindications for aspirin.…”
Section: Introductionmentioning
confidence: 99%
“…6 An increased bleeding risk is particularly ominous when treating ischemic cerebrovascular disease because of the harmful consequences of intracranial hemorrhage; 7 therefore, ischemic cerebrovascular disorders represent a clinical setting in which an antiplatelet regimen with a lower bleeding risk would be of special value. 8,9 Antiplatelet therapy with aspirin, dypiridamole, clopidogrel, or their combination is the mainstay for secondary prevention of stroke, but its effectiveness for acute stroke is limited and is associated with increased intracranial bleeding. 10 Intravenous GPIIb/IIIa inhibitors, effective in acute coronary syndromes, 11 have given disappointing results in acute ischemic stroke: a recent phase 3 trial with abciximab was stopped prematurely because of increased intracranial hemorrhage and mortality and lack of efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Patients who participated in these trials may not have been representative of patients with a recent TIA or ischemic stroke in general. We and others [3][4][5] showed that patients in antiplatelet trials are generally younger, have less comorbidity, and less severe strokes than patients in hospital and population surveys. This may raise concerns about extrapolation of trial results to all patients with a recent TIA or minor ischemic stroke.…”
mentioning
confidence: 89%